Intelligent control of rehabilitation robot: Auto tuning PIDController with interval type 2 fuzzy for DC servomotor - Nhon, P.N.Q. (Elsevier B.V., 2014)
DC servomotors have been in use extensively for many applications vary from industrial to robotics to consumers. DC servomotors provide error feedback signal to its PID controller to minimize the error. However, its conventional PID controller still causes several problems such as poor accuracy in non-linear systems and poor response when there is frequent disturbance. In this research, atuning method for PID controller, i.e., Interval Type-2 Fuzzy Logic for DC servomotor is proposed. The paper proposes error and error derivative are oftype 2 fuzzy inputs to the rules and output is the corrective signal to supplement PID output. Detailed methodology and work results show that both type-1 and type-2 fuzzy logic tuning offers better response than conventional PID controller and Interval Type-2 Fuzzy Logic handles uncertainties better that Type-1. Thiscould be used as intelligent control in Rehabilitation Robots. In addition, italso provides promising potentials in robotics and medical applications that require high precision and quick response such as medical diaphragm pump, infusion pump, pharmaceutical dispenser, minimally invasive surgery, etc. Â© 2014 The Authors.